2009
DOI: 10.1182/blood-2009-04-218727
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen α and γ genes and factor VLeiden in children with thromboembolism: results from 2 family-based association studies

Abstract: Previous case-control studies showed that genetic variation in the fibrinogen ␥ gene (FGG) increased the risk for deep vein thrombosis (VT) in adults. We investigated the association between the fibrinogen ␣ (FGA) and FGG haplotypes, the factor V Leiden -mutation, and pediatric VT and thromboembolic stroke (TS) in 2 independent study samples. Association analysis revealed that the FGA-H1 and FGG-H2 haplotypes were significantly overtransmitted to VT patients (FGA-H1, P ‫؍‬ .05; FGG: H2, P ‫؍‬ .032). In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…93 A recent German study showed that the same H2 was significantly more prevalent in VT patients and significantly associated with thromboembolic stroke. 91 No association of this SNP was found with risk of MI. 94 SNP 9340T3C was associated with increased ␥A/␥Ј fibrinogen levels, again confirmed in other studies, 84,87,91 and a slight decrease in DVT risk.…”
Section: Determinants Of the ␥A/␥ Fibrinogen Levelmentioning
confidence: 79%
See 3 more Smart Citations
“…93 A recent German study showed that the same H2 was significantly more prevalent in VT patients and significantly associated with thromboembolic stroke. 91 No association of this SNP was found with risk of MI. 94 SNP 9340T3C was associated with increased ␥A/␥Ј fibrinogen levels, again confirmed in other studies, 84,87,91 and a slight decrease in DVT risk.…”
Section: Determinants Of the ␥A/␥ Fibrinogen Levelmentioning
confidence: 79%
“…91 No association of this SNP was found with risk of MI. 94 SNP 9340T3C was associated with increased ␥A/␥Ј fibrinogen levels, again confirmed in other studies, 84,87,91 and a slight decrease in DVT risk. 81 In addition, 9340T3C was associated with a reduced risk in a Swedish MI study, 94 a Dutch study on ischemic stroke, 87 but not in a Dutch study on MI.…”
Section: Determinants Of the ␥A/␥ Fibrinogen Levelmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, we examined the association between genetic variation in FGG and FGA genes and plasma levels of ␥A/␥Ј fibrinogen in the group of VT children. 1 We found in an independent study sample that For personal use only. on May 10, 2018. by guest www.bloodjournal.org From risk of VT and TS in children, and (2) the observed negative correlation of genetic VT risk with the plasma levels of the fibrinogen ␥Ј variant suggests that FGG-H2 and -H3 haplotypes modify thrombosis risk by controlling the level of this FGG splice isoform.…”
Section: Elevated Fibrinogen ␥ Ratios and Clinical Outcomesmentioning
confidence: 93%